Sizing effects on the interfacial shear strength of a carbon fibre reinforced two-component thermoplastic polymer. (December 2019) - Hendlmeier, Andreas; Marinovic, Lucas I.; Al-Assafi, Salwan; Stojcevski, Filip; Henderson, Luke C.
Abstract: Here carbon fibre surface treatment conditions (current, bath conductivity, and sizing) gave a comprehensive set of 27 unique carbon fibre samples. Examination of the interfacial shear strength (IFSS) in a two-component polymethyl methacrylate resin via the V-notch shear test. Epoxy-sized fibres show a strong dependence on surface treatments and were widely variable (25.6 ± 0.72 to 38.5 ± 2.69 MPa). We suggest the epoxy sizing is soluble in the methylmethacrylate monomer and is removed from the surface before complete polymerisation. Adhesion in epoxy-sized fibres seemed linked to the ratio of oxygen and nitrogen on the fibre surface (determined by XPS). Polyamide-sized fibres possessed a smaller data variation (37.3 ± 3.34 to 33.4 ± 3.18 MPa), suggesting the polyamide-sizing masks the underlying surface chemistry of the fibre induced by the variations in surface treatment. A hybrid of these two outcomes was observed with the polyurethane sized fibres (36.1 ± 2.19 to 28.8 ± 2.82 MPa), suggesting a mixture of effects observed above.